2016
DOI: 10.1097/iae.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Dilated Fundus Photography and Near Visual Acuity Testing as Inexpensive Screening Tools to Detect Referral Warranted Diabetic Eye Disease

Abstract: The authors report a smartphone-based telemedicine system that demonstrated sensitivity and specificity to detect referral-warranted diabetic eye disease as a proof-of-concept. Additional studies are warranted to evaluate this approach to expanding screening for diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
95
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 36 publications
5
95
0
2
Order By: Relevance
“…Although Myung et al demonstrated that the EyeGo is easy for medical professionals to use, the device remains relatively untested by users without training in eye care 14. Consequently, our primary aim was to evaluate the ability of untrained users to quickly capture high-quality images of the front of the eye, and our secondary aim was to assess the relationship between a user’s age, comfort using a smartphone, and comfort in assessing problems with the eye and the user’s ability to capture high-quality images of the front of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Although Myung et al demonstrated that the EyeGo is easy for medical professionals to use, the device remains relatively untested by users without training in eye care 14. Consequently, our primary aim was to evaluate the ability of untrained users to quickly capture high-quality images of the front of the eye, and our secondary aim was to assess the relationship between a user’s age, comfort using a smartphone, and comfort in assessing problems with the eye and the user’s ability to capture high-quality images of the front of the eye.…”
Section: Introductionmentioning
confidence: 99%
“…There is particularly great interest in the validation and integration of smartphone-based retinal photography in local community screening programs for diseases such as glaucoma and diabetic retinopathy (DR) [13][14][15][16] , as well as in the emergency department and inpatient settings where the fundus examination is under-performed [17][18][19] . DR is the most common microvascular complication of diabetes and the leading cause of vision loss in working-age adults aged 20 to 74 in the United States, accounting for 12% of new cases annually [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, imaging by non-expert operators may affect image quality and is an important consideration for community-based screening efforts 37,38 . Several studies have investigated smartphone-based screening of DR 4,16,39 and reported sensitivities of ≥80% with high specificities, as recommended by the British Diabetic Association for new imaging devices in population-based screening 40 . However, other investigators have found insufficient sensitivities of below 60% for detecting DR 37 suggesting smartphone imaging is not universally reliable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Toy et al compared images taken with a subsequent iteration of this device with in-person slit-lamp biomicroscopy for grading diabetic retinopathy and found 90% agreement between the two methods; moreover, they found that the photograph grade was 91% sensitive and 99% specific, with a 95% positive predictive value and a 98% negative predictive value, for diabetic disease in their patient population. 12 These devices were the early prototypes of a now-commercially available device known as Paxos Scope™ (DigiSight Technologies, San Francisco, CA, USA) that was registered in 2015 with the United States Food and Drug Administration (FDA) as a 510(k) Class II exempt ophthalmic camera for both anterior and posterior segment photography. In parallel efforts, Maamari et al (2014) described a digital fundus imaging device for taking high quality wide field retinal photographs, 13 while Russo et al (2015) published a study using a direct ophthalmoscopy adapter (D-Eye) for diabetic screening, which also showed excellent agreement between in-person and smartphone image-based retinopathy grading.…”
Section: Introductionmentioning
confidence: 99%